1987
DOI: 10.1073/pnas.84.11.3787
|View full text |Cite
|
Sign up to set email alerts
|

Kinds of mutations formed when a shuttle vector containing adducts of (+/-)-7 beta, 8 alpha-dihydroxy-9 alpha, 10 alpha-epoxy-7,8,9, 10-tetrahydrobenzo[a]pyrene replicates in human cells.

Abstract: Kinds of mutations formed when a shuttle vector containing adducts of (±+)-7,8,8a-dihydroxy-9a,10a-epoxy-7,8,9,10- ABSTRACTWe have investigated the kinds of mutations induced when a shuttle vector containing covalently bound residues of (±)-7p,8a-dihydroxy-9a,10a-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (BPDE) replicates in human cells. A human embryonic kidney cell line, 293, was used as the eukaryotic host. The target gene for mutation analysis, supF, codes for a tyrosine suppressor tRNA and is strategically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 39 publications
4
50
1
Order By: Relevance
“…This difference may be due to the fact that the V79-4 cells used here are a clone of the original V79 cell line and may be more genetically unstable. When the background mutant frequency is subtracted, however, the data is consistent with previously published data which show that nickel is a weak mutagen [Morita et al, 1991;Hartwig and Beyersmann, 1989a], and BPDE is a relatively strong mutagen [Yang et al, 1987]. In addition, the results are consistent with the reports from other laboratories which report an additive or synergistic response when various nickel compounds are combined with benzo[a]pyrene Sanner, 1980, 1981;Uziel et al, 1986, Christie, 1989.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This difference may be due to the fact that the V79-4 cells used here are a clone of the original V79 cell line and may be more genetically unstable. When the background mutant frequency is subtracted, however, the data is consistent with previously published data which show that nickel is a weak mutagen [Morita et al, 1991;Hartwig and Beyersmann, 1989a], and BPDE is a relatively strong mutagen [Yang et al, 1987]. In addition, the results are consistent with the reports from other laboratories which report an additive or synergistic response when various nickel compounds are combined with benzo[a]pyrene Sanner, 1980, 1981;Uziel et al, 1986, Christie, 1989.…”
Section: Discussionsupporting
confidence: 93%
“…When these adducts are left unrepaired, they can result in many types of mutations, including base substitutions [Eisenstadt et al, 1982], frame shifts [Mizusawa et al, 1981], deletions [Wei et al, 1984], and duplications [Pall and Hunter, 1987]. The most predominant mutations are base substitutions, with G:C to T:A transversions being the most common [Mazur and Glickman, 1988;Yang et al, 1987]. These base substitutions are presumably produced by the DNA polymerase during replication due to the fact that the polymerase cannot recognize the modified base and inserts an incorrect base in the newly synthesized DNA strand.…”
Section: Introductionmentioning
confidence: 99%
“…Cell survival is unaffected by the status of the supF gene. Single or tandem base substitution mutations at 54% of the basepairs (75 of 139 basepairs from basepair 42 to basepair 180) have been found to reduce expression of the supFgene (8,(11)(12)(13), and our unpublished observations). No silent mutations have yet been identified.…”
Section: Methodssupporting
confidence: 59%
“…It was found that the strong and sequence-specific formation of BPDE-DNA adducts in p53 of bronchial epithelial cells in vitro occurred at the same positions as the major mutational hotspots in p53 found in DNA from human lung cancer tissue. Furthermore, other studies on cultured cells in vitro exposed to PAH, showed that aromatic carcinogens have the potential to alter or "activate" H-ras proto-oncogenes (Marshall et al, 1984;Vousden et al, 1986;Yang et al, 1987). In these studies, the most predominant point mutations induced by BPDE were G to T transversions and to a lesser extent G to A transitions, similar to those found in ras oncogenes and p53 tumor suppressor genes in human cancers (Vineis and Caporaso, 1995).…”
Section: Criteria For Dna Adducts As Biomarkers Of Exposure To Aromatmentioning
confidence: 57%